Gene polymorphisms in the interleukins gene and the risk of acute pancreatitis: A meta-analysis. (March 2019) - Zhu, Xiaole; Hou, Chaoqun; Tu, Min; Shi, Chenyuan; Yin, Lingdi; Peng, Yunpeng; Li, Qiang; Miao, Yi
Highlights: Genetic Polymorphisms might be a novel perspective on acute pancreatitis. Comprehensively describe interleukin polymorphisms combined with the risk associated with AP. Meta-analysis is a very powerful tool for analyzing cumulative data of studies. A significant association was found between the IL-8-251 T/A (rs4073) polymorphism and AP risk. A significant association was found between the IL-10-1082 A/G (rs1800896) polymorphism and AP risk. Abstract: Single nucleotide polymorphisms (SNPs) within the interleukins (IL) gene may affect the risk of acute pancreatitis. Many epidemiological studies have reported an association between the IL gene and acute pancreatitis risk, but the results remain inconsistent. Given the controversial available data, we carried out a meta-analysis to systematically evaluate and clarify the association between IL gene polymorphisms and AP. A systematic search of studies for this association was obtained from the PubMed, EMBASE, Web of Science and Chinese National Knowledge Infrastructure (CNKI) databases until June 1, 2017. We also searched the references of the included studies to identify additional studies. Odds ratios (ORs) with 95% confidence intervals (95% CIs) were used to pool the effect size. Stata12.0 was used for whole statistical analysis. Fifteen studies that contained 3371 AP cases and 3506 controls were included in final combination. Overall, a significant association was found between the IL-8-251 T/A (rs4073) polymorphism, the IL-10-1082 A/G (rs1800896) polymorphism and the AP risk in four genetic models (homozygote model, recessive model, dominant model, allele model). Meanwhile, individuals with IL-1β+3954 C/T (rs1143634, (homozygote model, recessive model)), IL-1β -511 C/T (rs16944, (dominant model)) and IL-6-634C/G (rs1800796, (allele model)) polymorphism were associated with an increased risk of AP. No evidence of an association was found between IL and 10-592 C/A (rs1800872) and IL-10-819 C/T (rs1800871) polymorphism and AP risk.